Ooghoogte : Stedelijk Van Abbemuseum 1936-1986 : Deel II. - Fuchs, Rudi H.; Leering, Jean; Van Abbemuseum, Eindhoven (Eindhoven : Van Abbemuseum, 1986)
Kokoschka, Oskar ; Kosuth, Joseph ; Kounellis, Jannis ; Kruyder, Herman ; Kuijpers, Theo ; Kupka, Frantisek ; Lam, Wifredo ; Lataster, Ger ; van der Leck, Bart ; Leger, Fernand ; Lennarts, Johan ; Leroy, Eugène ; Lesak, Frantisek ; LeWitt, Sol ; van der Linden, Thomas ; Lipchitz, Jacques ; Lippens, Guido ; Lissitzky, El ; Lohaus, Bernd ; Lohse, Richard Paul ; Long, Richard ; Louis, Morris ; Lucassen ; Lucebert ; Lüpertz, Markus ; Luyten, Mark ; Maaskant, Jan ; Mack, Heinz ; Manders, Jos ; Manessier, Alfred ; Mangold, Robert ; Manzoni, Piero ; De Maria, Nicola ; Matthys, Danny ; McLean, Bruce ; Merz, Gerhard ; Merz, Mario ; Messagier, Jean ; Mettig, Klaus ; Miro, Joan ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Morellet, François ; Morris, Robert ; van Munster, Jan ; Murphy, John ; Nanninga, Jaap ; Nauman, Bruce ; Nicholson, Ben ; Nijland, Dirk ; Nitsch, Hermann ; Nordman, Maria ; Oosterkerk, Ko ; Ouborg, Pieter ; Panhuysen, Paul ; Paolini, Giulio ; Pape, Erik ; Peeters, Henk ; Penalba, Alicia ; Penck, A.R. ; Penone, Giuseppe ; Permeke, Constant ; Picasso, Pablo ; Piene, Otto ; Pistoletto, Michelangelo ; Poliakoff, Serge ; Polke, Sigmar ; Poons, Larry ; Rabinowitch, Royden ; Raedecker, John ; Rainer, Arnulf ; Raveel, Roger ; Raysse, Martial ; Richter, Gerhard ; Roeland, Jan ; Rooskens, Anton ; van Rooyen, Joost ; Roth, Dieter ; Rückriem, Ulrich ; Ruscha, Edward ; Ryman, Robert ; Salle, David ; Sanders, Har ; Saura, Antonio ; Schonzeit, Ben ; Schoonhoven, Jan ; Schuhmacher, Wim ; Schwarzkogler, Rudolf ; Schwitters, Kurt ; Sieverding, Katharina ; Sluijters, Jan ; De Smet, Gust ; Sonderborg, K.R.H. ; Sonnier, Keith ; Spalletti, Ettore ; Stella, Frank ; Stoop, Pieter ; Struycken, Peter ; Tàpies, Antoni ; Tinguely, Jean ; Toorop, Charley ; Toroni, Niele ; Tuttle, Richard ; etc.
geboortedata per kunstenaar
Engels
Nederlands
Ooghoogte : Van Abbemuseum 1936-1986, Van Abbemuseum Eindhoven, 14 juni - 9 november 1986
boek